Improving postoperative care for neurosurgical patients by a standardised protocol for urinary catheter placement: a multicentre before-and-after implementation study - Ewout W Steyerberg; Anja H Brunsveld-Reinders; Wilco Peul; Wouter R van Furth; Jeanne-Marie Nollen (BMJ Open Quality)
Introduction Urinary catheterisation, including indwelling and clean intermittent catheterisation, is common in perioperative and postoperative care. Despite guidelines, practice variation is significant. Inappropriate catheterisation risks include urinary tract infections and reduced mobility, leading to prolonged hospital stays and increased antibiotic use. This study aims to improve postoperative care through appropriate catheterisation in neurosurgical groups frequently subjected to catheterisation.Methods We conducted a multicentre, before-and-after study in four Dutch hospitals from June 2021 to January 2023, including adult neurosurgical patients who underwent pituitary gland tumour or spinal fusion surgery. Exclusion criteria included conditions requiring chronic catheter use. A multifaceted strategy was implemented, focusing on a uniform protocol, an educational programme and department-specific champions. The primary outcome was inappropriate catheterisation, analysed with ordinal logistic regression. Secondary outcomes included total catheterisations, urinary tract infections and length of hospital stay. Ethical approval was obtained. Strengthening the Reporting of Observational Studies in Epidemiology and SQUIRE checklists were used.Results Among 3439 patients screened, 2711 were included, with 544 in the after group. The percentage of patients without inappropriate indwelling catheterisation increased from 46% to 57%, and the proportion without inappropriate clean intermittent catheterisation rose from 34% to 67%. Additionally, overall catheter use decreased: the percentage of patients not receiving an indwelling catheter increased from 54% to 64%, while those not requiring clean intermittent catheterisation rose from 89% to 92%. Infection rates and hospital stay were similar (1.4% and 1.3%; 4.9 and 5.1 days, respectively).Conclusions Implementing a uniform protocol may significantly reduce inappropriate and overall catheterisation in neurosurgical patients, aligning with patient-centred, less invasive healthcare. Ongoing education and adherence to standardised protocols are crucial. Future research should assess the long-term sustainability of these strategies.